2012
DOI: 10.1097/igc.0b013e318263ef34
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillar Type I Collagen Matrices Enhance Metastasis/Invasion of Ovarian Epithelial Cancer Via β1 Integrin and PTEN Signals

Abstract: These findings indicate that fibrillar type I collagen, by modulating integrin-PTEN/PI3K/Akt signaling pathway in remodeling ECM, is very important in affecting the invasion of aggressive ovarian cancer cells. Moreover, these data provide direct evidence for pathological ECM remodeling and cell signaling networks involved in the invasion of ovarian cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…Along with this finding, a paper has shown that fibrosis with type I collagen enrichment at the metastatic site can trigger the dormant-to-proliferative switch in dormant tumor cells leading to metastatic disease [44]. Recently, Shen and colleagues showed that fibrillar type I collagen is important in affecting the invasion of aggressive ovarian cancer cells [45] and Nguyen-Ngoc et al demonstrated metastatic mammary tumors to preferentially disseminate in specific ECM microenvironment containing also type I collagen [46]. More interestingly, transcriptomic dissection of OTSCC patient samples has revealed enhancements in e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Along with this finding, a paper has shown that fibrosis with type I collagen enrichment at the metastatic site can trigger the dormant-to-proliferative switch in dormant tumor cells leading to metastatic disease [44]. Recently, Shen and colleagues showed that fibrillar type I collagen is important in affecting the invasion of aggressive ovarian cancer cells [45] and Nguyen-Ngoc et al demonstrated metastatic mammary tumors to preferentially disseminate in specific ECM microenvironment containing also type I collagen [46]. More interestingly, transcriptomic dissection of OTSCC patient samples has revealed enhancements in e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Collagen remodeling by compaction is an important process for maintenance of tissue homeostasis [58][59][60] particularly following wound healing [61,62] and during scar formation [63,64], and is a hallmark of the invasive behavior of cancer cells as they migrate through connective tissues [65][66][67]. PAK1 has been implicated in cell behavior that affects matrix remodeling including the ability of cells to generate extensions [31,68], ECM contraction [35], membrane ruffling [69] and the secretion of matrix metalloproteinases [70].…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 collagen might have another supportive role as a scaffold of CD133‐positive GSCs to invade surrounding tissue. Type 1 collagen enhances invasion of some other cancers via integrin‐stimulated phosphoinositide 3‐kinase (PI3K)/Akt pathway . Akt signal is deeply involved in cell migration with matrix metalloprotease 9 in GBM .…”
Section: Discussionmentioning
confidence: 99%